2019
DOI: 10.2340/16501977-2558
|View full text |Cite
|
Sign up to set email alerts
|

Chronic pian in intensive care unit surviviors: incidence, characteristics and side-effects up to one-year post-discharge

Abstract: The sickest patients in a hospital often need treatment in an intensive care unit. When these patients eventually go home they often experience continuing psychological and physical problems, including pain. The aim of this study was to look at how often pain occurred in this group of patients, where the pain occurred, and if the pain was interfering with patient's lives. We studied 47 patients after discharge from hospital and found that two-thirds of them had pain that they did not have before their stay in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 17 publications
0
35
0
1
Order By: Relevance
“…17 The mental health effects of surviving COVID-19 may be further compounded by loneliness and isolation, job and economic loss, increased child care and familial responsibilities, and guilt if family members or other contacts contract the virus. Finally, COVID-19 survivors may experience chronic pain, which is commonly reported by ICU survivors, 18 potentially compounding the epidemic of opioid misuse already affecting many of the same vulnerable populations.…”
Section: Discussion and Policy Implicationsmentioning
confidence: 99%
“…17 The mental health effects of surviving COVID-19 may be further compounded by loneliness and isolation, job and economic loss, increased child care and familial responsibilities, and guilt if family members or other contacts contract the virus. Finally, COVID-19 survivors may experience chronic pain, which is commonly reported by ICU survivors, 18 potentially compounding the epidemic of opioid misuse already affecting many of the same vulnerable populations.…”
Section: Discussion and Policy Implicationsmentioning
confidence: 99%
“…This may be due to the high number of post-operative patients who were included in this analysis. However, recent data has shown that there is a high prevalence of pain problems in survivors of critical illness (Battle et al 2013, Hayhurst et al 2018, which can have a profound impact on daily activities and long term quality of life (Devine et al 2019). Clinicians in critical care must ensure that all is done within and during the critical care stay to manage pain.…”
Section: The Critical Care Environmentmentioning
confidence: 99%
“…Puntillo et al reported that half of the procedures in ICUS such as endotracheal and tracheal suctioning, chest tube removal, wound drain removal, turning, and arterial line insertion, increased the risk of patients having higher degrees of pain distress by at least 30% [8]. In addition, 38.2-66% of the intensive care survivors experience chronic pain up to one year after discharge [9,10]. erefore, the perception of a stressful experience is a key to recover from a critical illness: staff and family members should carefully evaluate different stressors while trying to avoid over-and underestimation [11].…”
Section: Introductionmentioning
confidence: 99%